Answer:
12x3+6x2+34x+17
Step-by-step explanation:
(2x+1)(6x2+8+9)
=(2x+1)(6x2+8+9)
=(2x)(6x2)+(2x)(8)+(2x)(9)+(1)(6x2)+(1)(8)+(1)(9)
=12x3+16x+18x+6x2+8+9
=12x3+6x2+34x+17
If you finish the question I may be able to answer it. ^^
Answer:
what is your question there is no equation
Answer:
Answer would be 9y+36
Step-by-step explanation:
Because if you distribute the 9 inside the parenthesis, you'd get
9*y=9y and 9*4=36
so 9y+36
Hope my answer was helpful to you!
Answer:
7.8
Step-by-step explanation: